Colour stability of the flowers in some modern rose varieties in Hungary - Boronkay, G.; Jámbor-Benczúr, E.; Máthé, Á. (International Journal of Horticultural Science, 2007)
A variety trial has been carried out to study the colour changing — colour stability of the flowers of some modern roses, especially of Hungarian varieties. 100 floribundas and polyanthas were observed. Colours of the petal surface were examined at three fenological stages of the flowers: at the bud, at the young open flowers and at the aged open flower stages. The colour difference was described in HLS standard. Our work shows that valuable Hungarian varieties can be found in both studied classes, but more floribundas bred in Hungary had good colour stability than polyanthas. The best Hungarian floribundas were 'Pest' and 'Remenyik Sándor emléke', although 'Regen', `Szent Lász1ó emléke' and 'Szabó Dezső emléke' were quite good. The best Western-European floribunda rose was 'Perneille Poulsen'. Their colour stability was reliable in different situations. Colour changing of the two best varieties was almost unperceivable from the bud to the young petals and from the young to the aged petals. In the polyantha class there was only one perfect variety: the Czech `Cs1 Cerveny Kriz'. The 'Fairy Damsel' was almost excellent as well. The best Hungarian polyanthas were `Domokos Pál Péter emléke' and 'Savaria'.